Microbial Dysbiosis in Pediatric Patients with Crohn's Disease - Kaakoush, Nadeem O. (American Society for Microbiology, 2012)
Microbial dysbiosis has been suggested to be involved in the pathogenesis of Crohn's disease (CD); however, many studies of gut microbial communities have been confounded by environmental and patient-related factors. In this study, the microbial flora of fecal samples from 19 children newly diagnosed with CD and 21 age-matched controls were analyzed using high-throughput sequencing to determine differences in the microbial composition between CD patients and controls. Analysis of the microbial composition of specific bacterial groups revealed that Firmicutes percentages were significantly lower in CD patients than in controls and that this was due largely to changes in the class Clostridia. Bacteroidetes and Proteobacteria percentages were higher and significantly higher in CD patients than in controls, respectively. Both the detection frequencies of Bacteroidetes and Firmicutes correlated (positively and negatively, respectively) with the calculated pediatric Crohn's disease activity index scores of patients. Upon further analysis, differences in the microbial compositions of patients with mild disease and moderate to severe disease were identified. Our findings indicate that a combination of different bacterial species or a dynamic interplay between individual species is important for disease and is consistent with the dysbiosis hypothesis of CD.